Efficient metal-organic framework adsorbents for removal of harmful heavy metal Pb(II) from solution: Activation energy and interaction mechanism. Issue 2 (April 2023) - Wang, Hao; Wang, Shuai; Wang, Shixing; Fu, Likang; Zhang, Libo
Abstract: Because of its irreversible toxicity and harm to people's health, lead contamination has gotten a lot of attention. As a result, the development of low-cost, high-performance removal approaches has become a popular issue. In this work, novel metal-organic framework (AMO-MOF) was developed to selectively adsorb Pb(II) from water. AMO-MOF perfectly inherits the structural characteristics of mesoporous materials and its specific surface area is 255.251 m 2 /g. The adsorption reached equilibrium at 180 min and the maximum adsorption capacity of AMO-MOF for Pb(II) was 472.73 mg/g. The adsorption of Pb(II) on AMO-MOF was fitted with pseudo-second-order kinetics and Langmuir isotherm models, indicating that the adsorption was monolayer chemisorption process. Thermodynamic and activation energy ( Ea ) analyses indicate that the monolayer chemisorption of Pb(II) on AMO-MOF was an endothermic process. When multiple cations coexist, AMO-MOF exhibits excellent selectivity for Pb(II). Meanwhile, after repeated used for 5 times, the removal rate can still reach more than 80 %. The adsorption mechanism is mainly the chelation and electrostatic interaction of N and O-containing functional groups on the adsorbent with Pb(II). The excellent adsorption performance of AMO-MOF for Pb(II) makes it have great application potential in practical environmental remediation. Graphical Abstract: ga1 Highlights: A novel organometallic framework (AMO-MOF) was successfully synthesized. The adsorbent displays a high adsorption capacity of 472.73 mg/g for Pb(II). The adsorbent had good selectivity and reusability. The activation energy ( Ea ) is − 33.59 kJ/mol. The adsorption mechanism was electrostatic attraction and chelation.